EVALUASI PEMAHAMAN KONSEP SISWA SMA/MA KELAS X PADA MATERI BESARAN VEKTOR DI KOTA METRO - Siti Khusnul Khotimah; Nengah Maharta; Wayan Suana (Unika Santu Paulus Ruteng, 2018)
This research aimed to determine the understanding level of the vector concept of Senior High School in Metro, Lampung province. The research populations were all students of X science Senior High School in Metro City, with the total number of schools was 27 Senior High School. The sampling technique in this research was using a stratified random sampling technique, so that obtained 288 students grade X science Senior High School at five Senior High Schools in Metro City. The five schools were SMA Negeri 1 Metro, SMA Negeri 5 Metro, SMA Kristen 1 Metro, SMAS Kartikatama Metro, and MAS Al Muhsin Metro. The result of the research shows that the students' understanding of the concept of students class X science Senior High School in the City of Metro on the subject matter of vector was included in the medium category, with the percentage of understanding concept were 58.0%, guessing were 25.0% and not understanding the concept were 17.0%. The most widely understanding subtopics of the students were a subtopic vector component with a percentage of 77.8%. The least understanding subtopics of the students were a subtopic value of vector with a percentage of 50.4%.